Use of Sectional Tray Design in Recording Edentulous Impressions for Microstomia Patients: A Case Report - Subba, A; Pathak, B; Suwal, P; Parajuli, PK; Sharma, A; Limbu, IK; Basnet, BB (Journal of Nepalese Prosthodontic Society, 2022)
Prosthetic rehabilitation of patients with microstomia presents a major challenge to dentist as limited oral opening makes access to the oral cavity for any dental procedure difficult. The primary hurdle during the fabrication of dentures in such patient is making an impression. This article describes the treatment of a patient with microstomia where maxillary and mandibular custom sectional impression trays were used for making definitive impressions.